Monitoring academic freedom: reflections for advocates - Andrea Boggio (Revista de Direito Econômico e Socioambiental, 2025)
This paper reflects on the challenges and opportunities of academic freedom monitoring from an advocacy perspective. Based on the review of two existing academic freedom indexes and the author’s experience building scientific freedom indicators, the paper discusses three challenges: conceptual, methodological, and political. The conceptual challenges are of four kinds: undertheorization, complexity, necessity of specification, and variation. The paper concludes by identifying three strategies (theory-building, interoperability, and cosmopolitanism) to strengthen monitoring and make it a more effective advocacy tool.